Controlling The Racing Vehicle on Motorcycles in The Satlantas of Gorontalo City - Siti Hardianti; Sukarman Kamuli; Nopiana Mozin (LEGAL BRIEF, 2021)
This study aims to provide an understanding of how the role of the police in controlling the use of racing exhaust in the city of Gorontalo. The problem is how the role of the police in controlling the racing exhaust in the city of Gorontalo; The research method used is a qualitative approach, namely by describing the data in the form of statements and information from informants that are adjusted to the reality in the field. Data collection techniques were carried out through interviews, observation and documentation; The results of the study can be concluded that the police to control racing exhaust do three ways to overcome violations of the use of racing exhaust, namely as follows: pre-emptive, preventive, and repressive.